Facile strategy for accessing 3-alkynylchromones through gold-catalyzed alkynylation/cyclization of o-hydroxyarylenaminones - Akram, Manjur O.; Bera, Saibal; Patil, Nitin T. (Chemical Communications, 2016)
A strategy based on tandem alkynylation of o-hydroxyarylenaminones followed by intramolecular cyclization has been developed to generate a diverse array of 3-alkynyl chromones. The functionality embedded in these key intermediates enables their facile elaboration into more diverse structures by a variety of functionalizations and ring-forming processes.